The Answer to the Lyre : Richard Bentley's Illustrations for Thomas Gray's Poems - Jestin, Loftus (Anniversary Collection., 2017)
In 1753 Robert Dodsley published Designs by Mr. R. Bentley, for Six Poems by Mr. T. Gray. Sponsored by Horace Walpole, this quarto was the first major aesthetic expression of the Strawberry Hill circle and a landmark in English book illustration.